S2 Vascular Quiescence Factor BMP9 is Regulated by Inflammation and Neutrophil Activation. (12th November 2015) - Li, W; Long, L; Hoenderdos, K; Upton, PD; Yang, X; Condliffe, AM; Chilvers, ER; Morrell, NW
Abstract : Introduction: Endothelial bone morphogenetic protein type II receptor (BMPR-II)-mediated signalling is essential for protecting vascular endothelium. Loss of BMPR-II predisposes human pulmonary artery endothelial cell (hPAEC) monolayers to apoptosis and increased permeability. In vivo, reduced BMPR-II function promotes endothelial permeability and the development of pulmonary arterial hypertension (PAH). Importantly, BMP9, the only confirmed active circulating BMP, signals preferentially via BMPR-II and induces BMPR-II expression to maintain endothelial integrity and homeostasis. It was recently shown that administration of recombinant BMP9 prevented LPS-induced lung vascular leakage in vivo and reversed established PAH in three rodent models. 1 However, it is not known how circulating BMP9 is regulated during LPS-induced inflammation and in PAH. Objective: To investigate whether BMP9 is regulated by inflammatory stimuli in vivo and in vitro . Results: Intraperitoneal LPS challenge in mice led to a significant increase in circulating neutrophil elastase levels with a reciprocal reduction in BMP9 levels (both measured by ELISA) within 24 h. Since this reduction in BMP9 might be due to reduced BMP9 synthesis in the liver or cleavage of BMP9 by neutrophil-derived proteases, we quantified BMP9 synthesis in the liver after LPS challenge, as well as changes in alpha-1 antitrypsin, the major elastase inhibitor in man. Synthesis of BMP9 fell sharply 3 h after LPS-challenge but recovered completely by 18 h. No increase in the synthesis or levels of circulating active alpha-1 antitrypsin was observed. Supernatants from purified human peripheral blood neutrophils activated in vitro degraded recombinant BMP9. Inhibition studies confirmed that the BMP9-cleavage activity released by activated neutrophils was largely attributable to neutrophil elastase. Conclusions and discussions: Synthesis of the endothelial protective factor BMP9 is actively regulated by inflammation, and BMP9 is subject to neutrophil elastase-mediated cleavage. Since inflammation has been shown to be a second hit in the pathogenesis of PAH, this study could provide a potential link between inflammation and reduced endothelial BMPR-II signalling. Reference: 1 Long L, Ormiston ML, Yang X, et al . Selective enhancement of endothelial BMPR-II with BMP9 reverses pulmonary arterial hypertension. Nat. Med . 2015;21 : 777–785